Testing for ethnic discrimination in outpatient health care: Evidence from a field experiment in Germany - Martin Halla; Christopher Kah; Rupert Sausgruber (Johannes Kepler University of Linz, Department of Economics, 2021)
To test for ethnic discrimination in access to outpatient health care services, we carry out an email-correspondence study in Germany. We approach 3,224 physician offices in the 79 largest cities in Germany with fictitious appointment requests and randomized patients' characteristics. We find that patients' ethnicity, as signaled by distinct Turkish versus German names, does not affect whether they receive an appointment or wait time. In contrast, patients with private insurance are 31 percent more likely to receive an appointment. Holding a private insurance also increases the likelihood of receiving a response and reduces the wait time. This suggests that physicians use leeway to prioritize privately insured patients to enhance their earnings, but they do not discriminate persons of Turkish origin based on taste. Still, their behavior creates means-based barriers for economically disadvantaged groups.
Keywords: I11; J15; I14; I18; H51; C93; 330; Discrimination; immigrants; ethnicity; health care markets; health insurance; inequality; correspondence experiment; field experiment